Isolation and functional identification of three cuticle protein genes during metamorphosis of the beet armyworm, Spodoptera exigua. Issue 1 (December 2017) - jan, Saad; Liu, Sisi; Hafeez, Muhammad; Zhang, Xiangmei; Dawar, Farman; Guo, Jiyun; Gao, Chao; Wang, Mo
Abstract The beet armyworm, Spodoptera exigua (Hubner), is one of the major crop pests and is a target for current pest control approaches using insecticides. In this study three cuticular protein genesCPG316, CPG860 andCPG4855 have been cloned from 0 h pupal integument ofS. exigua through race PCR Strategy. The deduced amino acid sequences were found to contain the RR-2 consensus region of other insect cuticular proteins and construct phylogenetic trees for each protein. Using quantitative RT-PCR, the developmental expression of the three genes through several larval and the early pupal stages was studied. All three genes contribute to the endocuticle althoughCPG316 may have a different role from the other two genes. All three newly isolated genes were analyzed and their functions were determined by using direct injection of the dsRNA into early 5th instar larvae. All genes are expressed in the larvae and early pupae but in different patterns. Furthermore, phenotypic results show that these genes have differing effects on the development of cuticle, its flexibility and a big role in metamorphosis in both larval and pupal stages.